Cat Swarm Based Shadow Detection Method - Firildak, Kazim; Karaduman, Mucahit; Talu, Muhammed Fatih; Yeroglu, Celaleddin (Ieee, 2018)
Innovations brought by developing technology are used in different forms in security area. Those technologies on imaging are usually involved in monitoring, tracking and detecting. When these processes are performed, the shadow of the object can prevent detection and monitoring. Therefore, in this study, a method has been proposed to determine the shadows of the objects and to distinguish them from the original image, and to determine the real image of the object. Previous work on this area has been done using classic shadow detection methods. In order to overcome their disadvantages during the detection period, this study uses cat swarm optimization, which can be applied to many problems. With this method, the shadows belonging to the object are detected, and the objects are determined by separating the shadows from the image. Later, if desired, follow-up of the object will also be achieved. It is shown that the suggested cat swarm optimization algorithm provides an effective result in shadow detection and give better results with shadow detection rate over compared algorithms.
Gölge Tespiti için Kedi Sürü Tabanli Yöntem
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Shadow detection; CSO; object detection